EXPLORING AWARENESS ON EVIDENCE-BASED PRACTICE AND RESEARCH UTILISATION IN CRITICAL CARE NURSES IN SELECTED HOSPITALS IN THE ETHEKWINI DISTRICT KWAZULU-NATAL - Almaze, J P; Emmamally, Waheedha (Africa Journal of Nursing and Midwifery, 2016)
In the critical care context, the complexity of patients’ conditions necessitates an evidence based approach to care that involves critical appraisal of available research and an amalgamation of research findings with clinical expertise and patient preferences to provide best care practices. Despite the rapid growth in research on best care practices in the critical care setting, the translation of these findings into practice has been slow. For an EBP culture to prevail in critical care areas, critical care nurses need to champion this practice and challenge traditional practices. This article explores the awareness of critical care nurses (CCNs) regarding evidence-based practice (EBP) and research utilisation in selected hospitals in the Ethekwini district in KwaZulu-Natal. A quantitative exploratory study design was used. A questionnaire, which included structured and open-ended questions, was used to collect data from a convenient clustered sample of CCNs from one tertiary public hospital and one private hospital. Of the 80 CCNs, 78.7% were familiar with the term EBP and 21.3% were unfamiliar with the term. The majority, 63%, of the CCNs responded positively regarding the importance of EBP. However they acknowledged many barriers, both personal and organisational, towards research utilisation. For a culture of EBP to prevail within critical care settings, hospital management must be committed to this initiative by providing all nurses with opportunities for training and incentives to nurses who are involved in EBP activities and research utilisation.